We share the Euro, but not our humanity: Humanity attributions are associated with the perceived causes, consequences, and solution to the Greek financial crisis. Issue 1 (2nd January 2021) - Sainz, Mario; Loughnan, Steve; Eyssel, Friederike; Pina, Afroditi
ABSTRACT: Political and financial crises are complex and multi-determined situations whose solutions depend on multiple factors. To understand these conflicts, we explore to what extent mutual outgroup dehumanization along with ingroup humanization between the parts involved in the conflict predict the interpretation of the different facets of the political situation (i.e. interpretation of the crisis, the perceived consequences, or the possible solutions). In this article, we focused on the dispute between Germany and Greece catalyzed by a Greek referendum in 2015. We assessed to what extent mutual (de)humanization between Germans and Greeks predicted the interpretation of the conflict. Our results showed a mutual dehumanization: Greeks mechanizing Germans and Germans animalizing Greeks. For Germans, dehumanizing the Greeks was linked to worse perceived Greek financial administration and minimizing the perception of the Greeks' suffering, whereas humanizing the ingroup was associated with more outgroup responsibility. For Greeks, dehumanizing the Germans was associated with a desire to avoid German financial control, whereas ingroup humanization was associated with better financial administration, less responsibility, and a higher perception of suffering among Greeks. In short, dehumanizing the other members of the European Union (EU) while humanizing their own nationality contributed to the neglect of the problems inside the EU, shaping the understanding of the economic conflict among both nations.